The Digitalization of Quality Management in Islamic Education Toward Quality Education: A Bibliometric Analysis of Scopus Trends - Muhammad Burhanuddin; Bunyamin Bunyamin; Ahmad Syaipul Bahri (Thawalib: Jurnal Kependidikan Islam, 2026)
This study identifies a critical gap in the Islamic education quality management literature: prior research remains largely conceptual, fragmented, and geographically limited, lacking an integrated global bibliometric mapping of digitalization and Total Quality Management (TQM). The purpose of this research is to analyze global research dynamics and develop an Islamic Digital Quality Management (IDQM) model that integrates Islamic values, TQM principles, and digital transformation as a strategic framework for sustainable quality improvement in Islamic education. The study employs a bibliometric method using Scopus data from 2017 to 2025, with PRISMA screening procedures and Boolean search strategies. Data analysis is conducted using Biblioshiny, VOSviewer, R, RStudio, and Excel to map publication trends, collaboration networks, and intellectual structures. The findings reveal a strong growth rate of 41.97 percent, particularly after 2020, indicating rapid digital transformation in the quality management of Islamic education. Key contributors include authors, institutions, and countries from both Muslim and non-Muslim contexts, reflecting increasing global collaboration. Keyword analysis shows dominance of digitalization, quality management, Islamic education, and Total Quality Management, with a shift toward data-driven approaches. However, international collaboration remains moderate at 22.73 percent, indicating the need for stronger research networks. The study concludes that digital transformation significantly reshapes the quality management of Islamic education through an integrated IDQM framework, while its significance lies in providing global, evidence-based mapping, strengthening international collaboration, and guiding sustainable policy development in Islamic education systems.